A study on marine clay as fine aggregate in microbial cement mortar mix. (2022) - Benjamin, Babitha; Lekshmi, Sreedevi; Zachariah, Serin; Sudhakumar, J.; Suchithra, T.V.
Abstract: The scarcity of natural resources like river sand pushes construction industries in search of alternative materials to replace fine aggregate in building construction. While working with such replacement materials, few drawbacks in mechanical properties is observed. In this study, marine clay was used as fine aggregate along with microorganism ( Bacillus. Subtilis MTCC441) to improve the mechanical properties of the mix. It was observed that a significant improvement in compressive strength and reduction in water absorption for microbial marine clay mortar mix compared to the control mix. The microbial excavated soil mixes could not show crack healing properties by bioprecipitation of calcium carbonate crystals. An induced crack of width 0.5 mm could not be healed when observed for 60 days with one-week intervals.